Altered Pharmacokinetics of Combined Oral Contraceptives in Obesity – Multi-Study Assessment - Luo, Dandan (Contraception, 2019)
OBJECTIVES: To evaluate the pharmacokinetics (PK) of levonorgestrel-containing combined oral contraceptives (COCs) in obese women. STUDY DESIGN: We pooled and reanalyzed data from 89 women with different BMI categories from four clinical studies. The levonorgestrel (LNG) and ethinyl estradiol (EE) PK were analyzed utilizing a zero-order absorption (K(0)), two-compartment PK model to evaluate key PK parameters in relation to a range of weights, body mass index (BMI), and body surface area (BSA). RESULTS: Increasing of body habitus metrics are correlated with decreasing C(max) (p<0.0001) and AUC(τ) (p<0.05) for both LNG and EE, but no correlation found for C(min) (p≥0.17). Increasing weight and BMI were associated with a modest increase (p≤0.056) of clearance (CL) and appreciable increases of central volume (V(1), p<0.05), distribution clearance (CLd, p≤0.001), and peripheral volume (V(2), p<0.0001) for LNG. For EE, increases in CL (p≤0.009) were found with greater weight, BMI and BSA. Values of V(1), CLd, and V(2) also increased (p<0.0001) in obese subjects. The half-life (T(1/2)) and steady-state volume (V(ss)) were greater among obese women (p<0.0001) for both LNG and EE. LNG and EE PK parameters correlated well (p≤0.006 for all), indicating that individual subject physiology affected both drugs similarly. CONCLUSIONS: The primary effects of obesity on LNG and EE were a modest increase in CL and a marked increase in distribution parameters. We observed no obesity-related differences in trough LNG and EE concentrations. IMPLICATIONS: This population PK analysis demonstrated reduced systemic exposure to LNG/EE oral contraceptives in obese subjects (C(max) and AUC(τ)); these particular differences are unlikely to lower contraceptive effectiveness among obese women who are correctly using LNG-containing contraceptives.